2015
DOI: 10.1200/jco.2014.59.0703
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab for Metastatic Renal Cell Carcinoma: Results of a Randomized Phase II Trial

Abstract: Purpose Nivolumab is a fully human immunoglobulin G4 programmed death–1 immune checkpoint inhibitor antibody that restores T-cell immune activity. This phase II trial assessed the antitumor activity, dose-response relationship, and safety of nivolumab in patients with metastatic renal cell carcinoma (mRCC). Patients and Methods Patients with clear-cell mRCC previously treated with agents targeting the vascular endothelial growth factor pathway were randomly assigned (blinded ratio of 1:1:1) to nivolumab 0.3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
706
1
13

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 961 publications
(740 citation statements)
references
References 39 publications
20
706
1
13
Order By: Relevance
“…Meanwhile, PD-L1 expression in tumor cells and inflammatory cells was associated with aggressive pathologic features and poor prognosis in patients with CCRCC [11]. Recently, PD-1/PD-L1 pathway blockade showed therapeutic benefit in patients with renal cell carcinoma (RCC) [12,13], thus being raised as a novel therapeutic strategy. In advanced non-small cell cancer, anti-PD-1 inhibitor (pembrolizumab) had an acceptable side effect profile and showed antitumor activity and PD-L1 expression in tumor cells correlated with improved efficacy of pembrolizumab [14].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, PD-L1 expression in tumor cells and inflammatory cells was associated with aggressive pathologic features and poor prognosis in patients with CCRCC [11]. Recently, PD-1/PD-L1 pathway blockade showed therapeutic benefit in patients with renal cell carcinoma (RCC) [12,13], thus being raised as a novel therapeutic strategy. In advanced non-small cell cancer, anti-PD-1 inhibitor (pembrolizumab) had an acceptable side effect profile and showed antitumor activity and PD-L1 expression in tumor cells correlated with improved efficacy of pembrolizumab [14].…”
Section: Introductionmentioning
confidence: 99%
“…Although beneficial in preventing excessive or harmful inflammation under normal conditions, in the context of cancer, tumor and stromal PD-L1 expression presents a barrier to immune function by contributing to the exhaustion of the antitumor lymphocytes that might otherwise clear the malignancy (6). Consequently, the PD-1:PD-L1 pathway has emerged as a critical target for cancer immunotherapy, and monoclonal antibodies that block either side of this inhibitory interaction have demonstrated impressive activity across a broad set of cancer subtypes, even at advanced and metastatic stages of disease (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Studies have demonstrated that after initial apparent disease progression, some patients derive clinical benefit from continued administration of immunotherapy [22,38,57,111,[118][119][120][121]. In a phase 3 study (CheckMate 025), 69% of patients with metastatic RCC treated with nivolumab beyond first progression subsequently demonstrated tumor reduction in target lesions, and almost half (48%) had a 30% reduction in tumor burden from baseline [111].…”
Section: Pseudoprogression With Icbsmentioning
confidence: 99%